The timing of administration of intravenous dexmedetomidine during lower limb surgery: a randomized controlled trial. Issue 1 (December 2016) - Kang, Eunsu; Lee, Ki; Jeon, Sang; Lee, Kyu; Ko, Myoung; Kim, Hyojoong; Kim, Yong; Jung, Jae-Wook
Abstract Background Dexmedetomidine, a selective alpha-2 agonist, has sedative, analgesic, and anxiolytic effects without respiratory depression. Dexmedetomidine can cause a biphasic cardiovascular response, and induce transient hypertension. Hypotension is a common complication of spinal anesthesia. Decreasing anxiety of patients before procedure is important for high quality of procedure. This study aimed to compare the incidence of hypotension and patients' anxiety and comfort levels when dexmedetomidine was intravenously administered before and after spinal anesthesia. Methods Seventy-four patients with American Society of Anesthesiologists physical status classification I or II were randomly allocated into two groups. Spinal anesthesia was performed using 12 mg of 0.5% heavy bupivacaine. In Group A, 1 μg/kg of dexmedetomidine was intravenously administered for 10 min, followed by the maintenance infusion of dexmedetomidine 0.2 μg/kg/hr after 5 min of intrathecal bupivacaine injection. Patients in Group B received same dose of dexmedetomidine by intravenous administration before 5 min of intrathecal bupivacaine injection. Perioperative vital signs, anxiety (using the Spielberger's State-Trait Anxiety Inventory) and comfort (using the numerical rating scale) were evaluated. Results The incidence of hypotension was significantly lower in Group A (16.1%) than in Group B (48.4%) during infusion of dexmedetomidine (p  = 0.01). The need for treatment of hypotension is higher in Group B than Group A (p  = 0.02). The incidence of bradycardia and desaturation did not significantly differ between the two groups. There were no statistically significant differences regarding the patients' anxiety and comfort. Conclusions Hypotension is more frequently occurred, and the treatment of hypotension is more needed in Group B. The intravenously administration of dexmedetomidine before spinal anesthesia has no advantages in hemodynamic status and patients' comfort compared to that after spinal anesthesia during lower limb surgery. Trial registration ClinicalTrials.gov number, NCT02155010 . Retrospectively registered on May 22, 2014.